2012
DOI: 10.1080/15283488.2012.716378
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Qualitative Extension for the Personally Expressive Activities Questionnaire (PEAQ-QE): A Construct Validation Study

Abstract: This study describes the development of a qualitative extension for the Personally Expressive Activities Questionnaire (PEAQ), a widely used quantitative questionnaire assessing feeling of personal expressiveness, a core positive identity construct. The PEAQ qualitative extension was developed as part of an ongoing effort to develop and refine an easy-to-use, standardized, reliable method designed for use in adding a free response qualitative component to a full range of fixed response quantitative measures. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Brief narratives about participants’ life goals were elicited using the Personally Expressive Activities Questionnaire–Qualitative Extension (PEAQ–QE; Rinaldi et al., ). Participants identified three life goals, selected their most important goal, and provided an open‐ended description of its meaning and significance.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Brief narratives about participants’ life goals were elicited using the Personally Expressive Activities Questionnaire–Qualitative Extension (PEAQ–QE; Rinaldi et al., ). Participants identified three life goals, selected their most important goal, and provided an open‐ended description of its meaning and significance.…”
Section: Methodsmentioning
confidence: 99%
“…Life goal narratives were coded using the theoretical coding categories developed by relational data analysis (RDA) and reported in Rinaldi et al. (). RDA draws on methods associated with grounded theory, a general methodology for generating theory from data that includes strategies such as open coding and constant comparison (Strauss & Corbin, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive outcome: Personally expressive life goals. The Personally Expressive Activities Questionnaire -Qualitative Extension (PEAQ-QE) (Rinaldi et al, 2012) adds an open-ended response component to the PEAQ to provide a method for eliciting the narrative/linguistic expressions of meaning and significance of participants' most important life goals. Specifically, participants were asked to identify up to three life goals and then to identify their most important life goal.…”
Section: Methodsmentioning
confidence: 99%
“…The Development of a Free-Response Performance-Based Indicator of Critical Evaluation As Rinaldi et al (2011) have noted, the use of qualitative free-response measures in developmental research broadens the scope of the investigation beyond the examination of properties identified as theoretically meaningful prior to conducting the research, i.e., as is usually done under cross-sectional and longitudinal quantitative research designs using fixed-response measures . Although there are many advantages to the use of such methods of data collection, an important limitation of their use is that fixed-response measures rule out in advance the possibility of detecting response properties that are uniquely meaningful (ordinary language meaning, theoretical meaning, or both) within a specific population not previously studied, qualitatively transformed, or involving temporal change (e.g., developmental, historical, longitudinal, or intervention change) resulting in newly emergent properties in a previously studied population .…”
Section: Study I: the Development Of The Critical Problem-solvinmentioning
confidence: 99%